How prepared are New Zealanders to achieve adequate consumption in retirement? : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Banking at Massey University, Manawatu, New Zealand - Lissington, Robert John (Massey University, 2018)
The majority of New Zealand retirees are happy with their current level of retirement income; however, the critical issue is “Will their financial resources last?” This question provides the catalyst for this thesis, requiring a definition for, and a way of measuring retirement adequacy that is appropriate for New Zealanders. Government-funded NZ Superannuation forms the foundation of New Zealanders’ retirement income, sufficient to cover basic needs and prevent retirees falling below the poverty line. Some (passive) retirees find that NZ Superannuation is sufficient to meet their needs, achieving retirement adequacy regardless of their financial behaviour and actions. However, others (active) retirees, desiring a higher retirement income, are required to make financial decisions and take action to augment their NZ Superannuation in order to achieve the lifestyle and level of consumption desired in retirement. While retiree retirement adequacy can be calculated with a degree of certainty, that is not the case for pre-retirees as future employment, income, and health are susceptible to change. This study found the Consumption Replacement approach was to be a more appropriate methodology than Income Replacement for measuring retirement adequacy. Financial calculations using data collected from an on-line survey of 1,044 respondents found that 60.4% of all ‘current’ retirees and 48.6% of 'active’ retirees were likely to be adequately prepared for retirement, by being able to maintain pre-retirement lifestyle and consumption in retirement. Significant retirement adequacy factors drawn from the data were used to develop the Financial Preparedness for Retirement (FPfR) Index to compare the preparedness of retirees to pre-retirees. This study found that fewer pre-retirees (32.1%) were likely to achieve retirement adequacy than retirees. Significantly, nine out of ten inadequately prepared pre-retirees would need to save more than 25% of their current household income pre-retirement in order to achieve their required retirement saving accumulation targets. The conclusion reached is that New Zealand pre-retirees are less prepared financially for retirement than current retirees. Findings from this thesis will help provide a greater understanding of retirement preparedness amongst policymakers, government agencies, educationalists, financial institutions, professional financial advisers, and others, both internationally and in New Zealand.
Keywords: Retirement income; Planning; Finance, Personal; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Business studies